ASSESSMENT OF THE HYDROLOGICAL REGIME OF THE SANGZOR RIVER (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This study presents an assessment of the hydrological regime of the Sangzor River basin using a multidisciplinary methodological approach. The analysis is based on long-term hydrological observations (2000-2023) of water discharge, flow volume, and turbidity provided by the Uzbekistan Hydrometeorological Service (Uzhydromet), as well as design and operational data from the Jizzakh Reservoir (2005-2023). Hydrological calculations included the determination of average, maximum, and minimum water discharges, coefficients of variation (Cv) and skewness (Cs), and flow modulus (l/s·km²). Seasonal distribution of flow was evaluated using the Gumbel distribution law, and return periods of maximum discharge (1%, 5%, and 10%) were estimated through probabilistic analysis. The results provide a reliable scientific basis for effective water resource management, irrigation planning, and ecological monitoring in the Sangzor River basin.